La sutura de los mundos. Políticas del lenguaje en Rubén Darío (El Hilo de la Fabula, 2018)
The work of Rubén Darío is a milestone that once again finds all its strength in the discussion of hegemonic paradigms in the field of Comparative Studies, the Weltliteratur, Hispanism and Transatlantic Studies, not as a case to be analyzed but as a place of theoretical enunciation that, as it could not be otherwise, anticipates some developments of postcolonial theory and subaltern studies.Darío (as Caupolican) not only supports a world on his back, but interrupts every illusion of homogeneity and arrogance in relation to any center. He tells us that the language and the poem are in an impossible place and finds in that impossibility a theoretical principle, an ontology of the present and of ourselves.
Keywords: Ruben Darío; Weltliteratur; Subaltern Studies; Comparatism; World